2021
DOI: 10.1080/00318884.2020.1857113
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular assessment of Grateloupia (Halymeniales, Rhodophyta) from Egypt revealed a new introduced species in the Mediterranean Sea, Grateloupia gibbesii

Abstract: The Mediterranean Sea is a hotspot for introduced marine species, including seaweeds. Among red algae, Grateloupia, with no less than eight introduced species, occupies a prominent position. Here, we report a large foliose Grateloupia species collected in Eastern Harbour, Alexandria, Egypt, which had previously been reported as G. acuminata and G. doryphora. Comparison of rbcL gene sequences revealed that the specimens represent G. gibbesii, a species originally described from Charleston, South Carolina, USA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The generic diagnostic features in the Halymeniaceae include a combination of auxiliary cell ampullae features, cystocarp morphology, and vegetative structure (Chiang 1970, Womersley and Lewis 1994, 2020 as well as gene phylogeny (Wang et al 2001, Hommersand et al 2010, Calderon et al 2014a,b, D'Archino et al 2015. However, the development of the auxiliary cell ampullar complex and carposporophytes is obscure and controversial in many genera, especially in the Grateloupia/Phyllymenia/Prionitis complex (Lin et al 2008, Gargiulo et al 2013, Rodr ıguez-Prieto et al 2021. The LSU+rbcL phylogenetic analyses in this study (see Fig.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The generic diagnostic features in the Halymeniaceae include a combination of auxiliary cell ampullae features, cystocarp morphology, and vegetative structure (Chiang 1970, Womersley and Lewis 1994, 2020 as well as gene phylogeny (Wang et al 2001, Hommersand et al 2010, Calderon et al 2014a,b, D'Archino et al 2015. However, the development of the auxiliary cell ampullar complex and carposporophytes is obscure and controversial in many genera, especially in the Grateloupia/Phyllymenia/Prionitis complex (Lin et al 2008, Gargiulo et al 2013, Rodr ıguez-Prieto et al 2021. The LSU+rbcL phylogenetic analyses in this study (see Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, Rodríguez‐Prieto et al. (2021: 85) did not use the words “here designated” in their attempted selection of a lectotype as required by ICN Art. 7.11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Algae were considered as good alternative for nematode control 57 . On the other hand, the use of nanoparticles such as nano silver has been adopted in the last few years to control plant pathogens including nematodes 30,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of nanotechnologies in many elds such as biology, medicine, pharmacology and as well as agriculture gave rise to the application of green silver nanoparticles as a new approach to control root knot nematodes 29,30 . Khan et al 31 reported that different seaweeds exhibited signi cant nematicidal activities such as: inhibition of egg hatching, increasement larval mortality and reduction of root-knot disease.…”
Section: Introductionmentioning
confidence: 99%